Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1063/1.1760236
|View full text |Cite
|
Sign up to set email alerts
|

Nearest-neighbor distances in strained thin films of random pseudobinary semiconductor alloys: A calculational methodology

Abstract: A method, based on macroscopic elastic theory, is presented, which predicts the nearest-neighbor distances in strained pseudobinary semiconductor thin films. The method applies to films grown on the (001) face of substrates with the zincblende or diamond structure. Based on crystallographic and elastic parameters, the bond lengths are determined through minimization of the elastic energy calculated in the framework of the valence force field method. Good agreement with experimental data is obtained by consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…By performing a combined fit of Ga and As K-edges spectra (see Figure 13b-c and Table 1), they observed a stretching of the As-Ga first shell bond distances and a contraction of the As-In first shell distances with respect to the binary compounds InAs and GaAs. These distances are in agreement with the experimental [168] and theoretical [389] data discussed in the previous Section for strained In x Ga 1x As alloys. Moreover, Mino et al noticed that ΔR As-Ga is higher in the SAG then in the FIELD region and an higher structural disorder (monitored by the σ 2 values) is observed in the SAG region, however the quality of the data resulted in too high error bars that did not allow them to reliably discriminate between SAG and FIELD regions (see Table 1).…”
Section: Mino Et Al [123] Investigated a Sag Eml Device Based On Al X...supporting
confidence: 90%
See 1 more Smart Citation
“…By performing a combined fit of Ga and As K-edges spectra (see Figure 13b-c and Table 1), they observed a stretching of the As-Ga first shell bond distances and a contraction of the As-In first shell distances with respect to the binary compounds InAs and GaAs. These distances are in agreement with the experimental [168] and theoretical [389] data discussed in the previous Section for strained In x Ga 1x As alloys. Moreover, Mino et al noticed that ΔR As-Ga is higher in the SAG then in the FIELD region and an higher structural disorder (monitored by the σ 2 values) is observed in the SAG region, however the quality of the data resulted in too high error bars that did not allow them to reliably discriminate between SAG and FIELD regions (see Table 1).…”
Section: Mino Et Al [123] Investigated a Sag Eml Device Based On Al X...supporting
confidence: 90%
“…In addition, successive polarization-dependent XAS measurements have shown that the second-and thirdshell interatomic distances of In x Ga 1-x As/InP epitaxial layers under tetragonal distortion split into two subset distributions [388]. Successively, d'Acapito proposed a method to calculate bond lengths in strained layers, based on a valence force field potential, that successfully matched with the experimental results [389]. This kind of approach has been very recently applied to investigate the local structure of CdSe/ZnSe systems [390].…”
Section: Semiconductor Heterostructures and Filmsmentioning
confidence: 71%
“…By performing a combined fit of Ga and As K-edges spectra (see Figure 15b-c and Table 5), they observed a stretching of the As-Ga first shell bond distances and a contraction of the As-In first shell distances with respect to the binary compounds InAs and GaAs. These distances are in agreement with experimental [125] and theoretical [126] data on strained In 0.60 Ga 0.40 As alloys on InP. Moreover they noticed that ΔR As-Ga is higher in the SAG then in the FIELD region and an higher structural disorder (monitored by the σ 2 values) is observed in the SAG region, however the quality of the data resulted in too high error bars that did not allow them to reliably discriminate between SAG and FIELD regions (see Table 5).…”
Section: Sag Fieldsupporting
confidence: 91%
“…Though a precise determination of the structure in case of elastic stress would require the knowledge of values of the elastic constants [34], we observed that the Mn-Ge distance did not change regardless of the Mn concentration. Our intent here was to give a first order rough estimate of the local strain as supported by the EXAFS determination of the first Mn-Ge distance close to 2.50 Å (see section 4).…”
Section: Near Edge Analysis (Xanes)mentioning
confidence: 70%